Thymic Carcinoma: A Review - Alqaidy, Doaa; Moran, Cesar A. (Frontiers in Oncology, 2022)
Thymic carcinoma represents a heterogeneous group of tumors with a wide morphologic spectrum. In the last decades, the interest to document this rare tumor in the literature including case reports and case sires of these tumors has expanded and the current use of immunohistochemical and molecular biology studies have, to some extent, expanded the conventional view of these tumors. Herein we review the most common morphologic subtypes, current concepts regarding the staging of these neoplasms, and the role of the ancillary studies in our daily practice, as well as discuss how it may impact treatment options.